Atomic segregation at twin boundaries in a Mg-Ag alloy. (15th March 2020) - Chen, X.F.; Xiao, L.R.; Ding, Z.G.; Liu, W.; Zhu, Y.T.; Wu, X.L.
Abstract: Segregation of solute atoms at twin boundaries (TBs) plays a critical role in mechanical properties and thermal stability of magnesium alloys. Here, segregation structures at {10 1 ¯ 1}, {10 1 ¯ 2} and {10 1 ¯ 3} TBs are characterized in a Mg-Ag alloy by means of the atomic resolution high-angle annular dark-field technique based on scanning transmission electron microscopy. Of particular finding is the unique complex segregation at {10 1 ¯ 3} TBs, where Ag atoms occupy both substitutional and interstitial sites. By contrast, Ag atoms only substitutionally segregate at {10 1 ¯ 1} and {10 1 ¯ 2} TBs. Calculation simulation of segregation energy and three-dimensional structure of TBs helps understanding of hybrid segregation.